도덕과교육에서 인성교육 관련 연구의 현황과 전망: 인성교육 5개년 종합계획을 중심으로 - 김현수; Kim Hyun-soo (윤리연구, 1(114), 2017)
인성교육진흥법 및 관련 법안에 대한 비판은 법안 자체의 타당성에 대한 비판,법안의 내용과 구성의 적합성에 대한 비판, 관련 법령의 시행의 어려움에 대한 비판의 세 측면에서 이루어지고 있다. 이러한 비판들은 인성과 인성교육이 올바른 방향으로 나아가야 한다는 문제의식에 기반하고 있다. 따라서 이러한 우려에 대하여 국가 교육과정을 통해 인성교육의 핵심 교과로 자리매김하고 있는 도덕과교육의 관점에서 응답할 필요성이 제기된다. 인성교육진흥법의 실질적 집행을 지원하기 위한 인성교육 5개년 종합계획은 불확실성을 기반으로 하는 미래 사회에 대하여 인성교육을 강화하기 위하여 지금 기울여야 할 노력과, 그 결과로 각 교육주체가 경험하게 될 이상적인 모습을 전망하고 있다. 이러한 인성교육에 대한 국가 수준의 계획과 전망 속에서 도덕과교육의 역할은 도덕과교육의 인성교육에 대한 연구 현황을 분석함으로써 점검할 수 있다. 도덕과교육의 교과내용학은 주로 동양사상 영역을 중심으로 적극적으로 이루어지고 있으며 서양사상 영역과 사회사상 영역에서의 연구가 함께 이루어지고 있다. 교과교육학영역에서는 인성교육의 효과적달성을 위한 교수학습방법 측면과 효과성 측정도구 개발 관련 연구가 이루어지고 있음을 확인할 수 있다. 인성교육 5개년 종합계획의 내용과 관련지어 볼 때 도덕과 교육과 인성교육의 향후 과제는 인성교육의 맥락에서 도덕과교육의 위상 정립에 대한 논의로 연결된다. 도덕과교육은 인성교육에 있어서 그에 상응하는 책무성을 지속적으로 수행하고 있음에도 불구하고 상대적으로 저평가되고 있는 부분이 있다. 이러한 문제를 극복하기 위해서 첫째, 도덕과교육 자체의 영역에서 인성교육과 관련한 연구가 더욱 활발하게 이루어질 필요가 있다. 둘째, 도덕과교육이 인성교육에 있어서 하나의 플랫폼의 역할을 수행하도록 구성될 필요가 있다. 셋째, 인성교육의 기반에 관한 이해가 도덕교육을 통해 개념적 정의에서 조작적 정의로 재해석 될 필요가 있다. Critics on the law on the character education is approached in following three ways: Firstly, validity of law itself. Secondly, suitability of the contents and structure of the law. Thirdly, difficulty of carrying the law into effect. These critics are based on the awareness of a problem that the character education should be continually progressed on the right direction. The Moral Education should be respond to these kinds of worries, for the Moral Education is designated as a supreme subject of the Character Education by the Korean National Curriculum. The Five-year Comprehensive Plan for the Character Education suggests that we should make a great effort for fortifying the Character Education to cope with uncertain future. And the plan also prospects ideal figure that each educational agents would experience as a result of the strengthening the Character Education. In this national level plan and prospect of the Character Education, the role of the Moral Education would be identified with the analysis of the current situation of the Moral Education in view of the Character Education. In the educational contents domain of the Moral Education, the Eastern thought actively approaches to the Character Education and the Western and the Social thought follows. In the subject matter education domain, teaching and learning method and quality measurement tool for the Character Education in view of the Moral Education is focuse on. The Moral Education executes the Character Education in practical. To make an advance for the Character Education, Firstly, researches on the Character Education in view of the Moral Education should be more actively performed, Secondly, the Moral Education would play a role as the Platform of the Character Educaion. Thirdly, approaching the foundation of the Character Education in the way of operational definition.